Livre-comércio dependente, lutas sociais e a formação de um campo antineoliberal na América Latina - Bocca, Pedro Paulo (2013)
This dissertation analyzes the Latin American political scenario after the failure of the proposed Free Trade Area of the Americas (FTAA), which represented the implementation of the neoliberal model in Latin America, sponsored by the United States and its allied different bourgeois factions in the different social formations in the region. To this proposal, a strong resistance led by social movements and leftist political parties emerged victorious, culminating in the election of progressive governments that, regard to the differences between them, seek an autonomy politics from the greatest imperialist power of our time. In this conjuncture of crisis in the U.S. hegemony, we examine three trends: an imperialist neoliberal offensive, a neo-developmental integration process, and the so called "Socialism of the XXI Century"